Indonesian politics and society a reader - Bourchier, David; Hadiz, Vedi R. 1964- (Routledge, Taylor & Francis Group, 2003)
Using an exhaustive selection of primary sources, this book presents a rich and textured picture of Indonesian politics and society from 1965 to the dramatic changes which have taken place in recent years. Providing a complete portrait of the Indonesian political landscape, this authoritative reader is an essential resource in understanding the history and contradictions of the New Order, current social and political conditions and the road ahead.